GESTÃO DE SISTEMA DE PROTEÇÃO CONTRA INCÊNDIO EM INSTALAÇÕES NUCLEARES: FATOR DE FORTALECIMENTO DO SISTEMA DE GESTÃO INTEGRADA - UM ESTUDO DE CASO - Santos, Joao Regis dos (2005)
The present study investigated and analyzed the importance of a system of integrated safety manage, environment and health in a nuclear installation, having as perspective, the fire protection manage. The inquiry was made using a qualitative research involving a case s study, where the considered environment was the Reconversion and UO2 Plant of the Indústrias Nucleares do Brasil (INB), located in Resende in Rio de Janeiro and the studied population, the managers and the staff directly involved with the aspects related to the safety of the industrial complex of the related company. The motivation for the research was the search of a bigger interaction of the questions related to the safety, environment and health in the nuclear industry having, as axle of the investigation, the fire protection. As a result, it was observed that in a nuclear installation, although dealing with diversified safety processes, integration is possible and necessary, since there are more reasons for integration than otherwise.